Improving Students' Writing Skills and Motivation in Learning English at SMAN 2 Kediri Using Hypnoteaching Strategy - Rosmarie, Aprilia; Mualimin, Mualimin (Jurnal Ilmu Pendidikan, 2021)
Writing is complex skills for EFL learners. In this Covid-19 pandemic, the teacher should held online learning to help students in learning. This study aimed to answer: (1&2) is there any significant improvement of students’ writing performance as were as the students’ motivation level after being taught with online Hypnoteaching strategy. The design of this study was a quasi-experimental study that used nonequivalent control group design. The researcher chose 70 students as the sample. The researcher applied online Hypnoteaching for 6 weeks. Result of the study showed that (1) the average gain for experimental group is 64.5343 and control group is 8.4054. The  Value (Sig) .000 greater than α, which means there is a significant improvement in writing skills after being taught with Hypnoteaching strategy; (2)The  Value Sig. (2-tailed) .003 greater than α. Thus, there is a significant difference on students’ motivation level after being taught with Hypnoteaching strategy. The researcher would explicate more on discussion part.